1996
DOI: 10.1111/j.1365-2958.1996.tb02494.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of mouse dendritic cells is triggered by listeriolysin, the major virulence determinant of Listeria monocytogenes

Abstract: Infection of a murine-spleen dendritic cell line by Listeria monocytogenes was found to induce cell death through apoptosis. To characterize the bacterial product(s) involved in induction of apoptosis, dendritic cells were infected with the L. monocytogenes EGD strain and several isogenic mutants deficient in the production of individual listerial virulence factors. The ability to induce cellular apoptosis was retained by all mutants tested, except the prfA and delta hly mutants, both of which are unable to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
137
1
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 186 publications
(146 citation statements)
references
References 30 publications
4
137
1
3
Order By: Relevance
“…Clonal analysis of MART1-specific CTLs has shown that MART1/T-cell receptor interactions are tightly restricted to HLA-A2, 37 and a recent study found that mature human MoDCs do not efficiently process and present the MART1 [27][28][29][30][31][32][33][34][35] epitope from whole MART1 due to the presence of the immunoproteasome, 38 suggesting that delivery of some whole proteins, including MART1, may not be an effective method of antigen delivery to DCs. Immature DCs express both the standard proteasome and immunoproteasomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clonal analysis of MART1-specific CTLs has shown that MART1/T-cell receptor interactions are tightly restricted to HLA-A2, 37 and a recent study found that mature human MoDCs do not efficiently process and present the MART1 [27][28][29][30][31][32][33][34][35] epitope from whole MART1 due to the presence of the immunoproteasome, 38 suggesting that delivery of some whole proteins, including MART1, may not be an effective method of antigen delivery to DCs. Immature DCs express both the standard proteasome and immunoproteasomes.…”
Section: Discussionmentioning
confidence: 99%
“…The presentation of the MART1 [27][28][29][30][31][32][33][34][35] epitope to the HLA-A2 molecule on MoDCs was examined by measuring IFN-␥ production by the CD8 ϩ T cells within the MART1-specific CTL population in response to E. coli-infected DCs. Immature DCs (10 5 cells, either HLA-matched and HLA-mismatched) were incubated with E. coli (at a ratio of 10 bacteria per DC for 16 hr) or pulsed with control peptides (10 g/ml, 1 hr).…”
Section: Antigen Presentation Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…GAS also elaborate the potent heterocyclic peptide cytolysin streptolysin S (SLS) [45] which can deplete host phagocytes and help promote bacterial survival [46] through a proinflammatory, calpaindependent cell death pathway [47] L. monocytogenes lyses the phagosomal membrane and escapes into the cytosol to initiate an intracellular infection, a process dependent on the pore-formin toxin listeriolysin O (LLO). Subsequently, intracellular L. monocytogenes induces LLO-dependent apoptosis in different cell types, including hepatocytes [48], lymphocytes [49] and dendritic cells [50]. LLO might insert into the mitochondrial membrane, allowing release of cytochrome c or efflux of Ca 2?…”
Section: Modulation Of Host Cell Apoptosismentioning
confidence: 99%